Pengaruh Flash Sale dan Live Streaming terhadap Pembelian Impulsif pada Marketplace Shopee di Kota Surabaya - Al Jonet, Arfad Syuqi Hikam; Purwanto, Sugeng; Ariescy, Reiga Ritomiea (J-MAS (Jurnal Manajemen dan Sains), 2024)
Current technological developments can change society to become modern and practical, for example the emergence of online shopping trends, such as on one of the online shopping platforms in Indonesia, namely Shopee. The Shopee marketplace offers various promotions such as flash sales and live streaming to attract consumers to make impulsive buying. The aim of this research is to test the effect of flash sales and live streaming on impulse buying on the Shopee marketplace in the city of Surabaya. The population in this research are consumers who have watched live streaming and are aware of the flash sale program on the Shopee marketplace domiciled in the city of Surabaya. This research used a quantitative approach by distributing questionnaires to 108 respondents via Google Forms. Research variables were measured using the Likert scale assessment technique levels 1-5. The analysis used in this research is Partial Least Square (PLS). This research shows the results that flash sales and live streaming have a significant positive effect on impulse buying on the Shopee marketplace in the city of Surabaya.